Analisis pengendalian biaya operasional terhadap peningkatan laba pada PT Aquwar Bintang Semesta - Evan Leandro Kho; Jullie J. Sondakh; Diana N. Lintong (Manajemen Bisnis dan Keuangan Korporat, 2026)
This study aims to analyze the effectiveness of operating cost control in supporting profit growth at PT Aquwar Bintang Semesta during the 2023–2024 period. The research employs a descriptive quantitative approach using variance analysis and the Operating Expense to Operating Revenue Ratio (BOPO) to evaluate cost efficiency. The data consist of budgeted and actual operating costs, operating revenues, and profit figures obtained from the company’s financial records. The results show that in both 2023 and 2024, total realized operating costs remained below the budgeted amounts, resulting in favorable variances of IDR 119,068,950 and IDR 91,042,900, respectively. Although several cost components experienced unfavorable variances, overall cost control was maintained effectively. The BOPO ratio slightly increased from 72.18% in 2023 to 72.45% in 2024, indicating a marginal decline in efficiency; however, the company still achieved higher profit growth in 2024. These findings suggest that effective operating cost control contributes positively to profit improvement, although continuous monitoring of specific cost components is required to enhance operational efficiency.